2004
DOI: 10.2176/nmc.44.420
|View full text |Cite
|
Sign up to set email alerts
|

Surgically Treated Aneurysm of the Trunk of the Persistent Primitive Trigeminal Artery-Case Report-

Abstract: A 62-year-old man presented with a very rare cerebral aneurysm arising from the trunk of the persistent primitive trigeminal artery (PPTA) manifesting as subarachnoid hemorrhage. Angiography showed a saccular aneurysm at the curved mid-section of the trunk of the left PPTA of the adult type. The patient underwent surgery via the left subtemporal approach, and the aneurysm was successfully eliminated by clipping without sequelae. Aneurysm formation at this point was probably due to hemodynamic stress. The perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The site of most reported PPTA aneurysms has been the curved trunk of the PPTA, suggesting that high hemodynamic stress initiates aneurysm formation. 27) In our case, the aneurysm was also situated on the curved trunk of the PPTA. Postoperative MR angiography indicated hypoplasia of basilar artery.…”
supporting
confidence: 46%
See 1 more Smart Citation
“…The site of most reported PPTA aneurysms has been the curved trunk of the PPTA, suggesting that high hemodynamic stress initiates aneurysm formation. 27) In our case, the aneurysm was also situated on the curved trunk of the PPTA. Postoperative MR angiography indicated hypoplasia of basilar artery.…”
supporting
confidence: 46%
“…27) There is no histological evidence supporting the hypothesis that pathological anomalies develop in the PPTA wall. Based on a review of 261 cases with PPTA reported between 1950 and 2003, 39 cases were identified with PPTA aneurysms.…”
Section: Discussionmentioning
confidence: 95%
“…Aneurysms of the PTA itself are quite rare (9,20), and arise either from the trunk of a PTA (76) or a PTA variant (26). Clinically, patients may present with sixth nerve palsy (46,57), subarachnoid hemorrhage (76) or carotid cavernous fistula secondary to rupture of these aneurysms (11) Direct surgical clipping (76), endovascular coiling (46,57) or stent-assisted coiling (48) have been employed to treat these aneurysms. As the perforating arteries originating from the PTA may be important in the supply of the hindbrain, PTA patency should be preserved if possible during surgery (76).…”
Section: (4) Carotid-cavernous Fistulamentioning
confidence: 99%
“…4 The lateral one gives perforating arteries to the pons. 4,7,8 Therefore, a brainstem infarction will occur following an inadequate occlusion of PTA. In the present case, the PTA belonged to the lateral type.…”
Section: Case Reportmentioning
confidence: 99%